Cross-linked density determination of natural rubber compounds by different analytical techniques - Hiranobe, Carlos Toshiyuki [UNESP]; Ribeiro, Gabriel Deltrejo [UNESP]; Torres, Giovanni Barrera; Dos Reis, Elton Aparecido Prado; Cabrera, Flávio Camargo; Job, Aldo Eloizo [UNESP]; Paim, Leonardo Lataro [UNESP]; Dos Santos, Renivaldo José [UNESP] (FapUNIFESP (SciELO), 2021)
This paper investigated the formation of crosslinks in natural rubber compounds in the vulcanization systems: conventional (CV), semi-efficient (SEV), and efficient (EV), processed with three types of accelerators: MBTS (dibenzothiazole disulfide), TMTD (tetramethylthiuram disulfide) and CBS (n-cyclohexyl 2-benzothiazole sulfenamide). The cross-linked densities were determined by organic solvent swelling, dynamic mechanical analysis (DMA), stress vs strain, and low-field nuclear magnetic resonance, the latter being the reference technique for comparison with the other results. It was found that the choice of accelerator type influences the processing time and the cross-linked density of the vulcanizate. The four techniques showed close values of cross-linked density for natural rubber compounds, demonstrating that the analytical techniques studied can be applied to determine crosslinked density.
Keywords: Cross-linked density; Flory-Rehner; Mooney-Rivlin; Natural rubber; NMR